Implicit Motives 2010
DOI: 10.1093/acprof:oso/9780195335156.003.0011
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 11 Factors That Influence the Relation Between Implicit and Explicit Motives: A General Implicit–Explicit Congruence Framework

Abstract: This chapter addresses the relation between implicit and explicit motives and focuses on factors that influence the degree to which an individual exhibits motive congruence (i.e., consistency between corresponding implicit and explicit motives). The chapter begins with a review of the extant empirical literature on motive congruence. A general conceptual framework based on the principles of structural equation modeling is proposed. Various theoretical perspectives on the processes through which congruence may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 74 publications
0
31
1
Order By: Relevance
“…Although implicit and explicit motives operate independently and correlate only weakly (Köllner and Schultheiss 2014;McClelland et al 1989) their coalition has been found to contribute to wellbeing and health (Brunstein et al 1998;Hofer et al 2006;Thrash et al 2010). Incongruence between implicit and explicit motives, in contrast, has been characterized as ''striving for goals without gaining pleasure from doing so'' or ''a lack of striving for goals which would give rise to positive affect'' (Langens and McClelland 1997;cf.…”
Section: Action Orientation and Motive Congruencementioning
confidence: 99%
“…Although implicit and explicit motives operate independently and correlate only weakly (Köllner and Schultheiss 2014;McClelland et al 1989) their coalition has been found to contribute to wellbeing and health (Brunstein et al 1998;Hofer et al 2006;Thrash et al 2010). Incongruence between implicit and explicit motives, in contrast, has been characterized as ''striving for goals without gaining pleasure from doing so'' or ''a lack of striving for goals which would give rise to positive affect'' (Langens and McClelland 1997;cf.…”
Section: Action Orientation and Motive Congruencementioning
confidence: 99%
“…To date, several dispositional moderator variables such as self-regulation competences have been identified (for a comprehensive overview see Thrash, Cassidy, Maruskin, & Elliott, 2010). In the realm of couple relationships, the partner's personality as well as characteristics of the relationship are likely additional moderators of the (in)congruence of relationship-specific motives.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…However, available evidence also indicates that individuals greatly differ from each other in their alignment of implicit and explicit motives. It seems that particular personality dispositions that are associated with moderate congruence of motivational systems (see Thrash, Cassidy, Maruskin, & Elliot, 2010). Taken together, these studies suggest that individuals vary in their capacity to access pre-consciously represented motives.…”
Section: Congruence Between Implicit and Explicit Motivesmentioning
confidence: 78%